Why do low-educated workers invest less in further training? - Didier Fouarge; Trudie Schils; Andries de Grip (Institute for the Study of Labor (IZA), 2010)
Several studies document the fact that low-educated workers participate less often in further training than high-educated workers. The economic literature suggests that there is no significant difference in employer willingness to train low-educated workers, which leaves the question of why the low educated invest less in training unanswered. This paper investigates two possible explanations: Low-educated workers invest less in training because of 1) the lower economic returns to these investments or 2) their lower willingness to participate in training. Controlling for unobserved heterogeneity that can affect the probability of enrolling into training, we find that the economic returns to training for low-educated workers are positive and not significantly different from those for high-educated workers. However, loweducated workers are significantly less willing to participate in training. This lesser willingness to participate in training is driven by economic preferences (future orientation, preference for leisure), as well as personality traits (locus of control, exam anxiety, and openness to experience).
Keywords: J24; J31; C21; 330; returns to training; preferences; non-cognitive skills; Bildungsertrag; Ungelernte Arbeitskräfte; Weiterbildung; Kognitive Fähigkeiten; Niederlande